The Effect of Green Hotel Implementation on Environmental Conservation at the Meru Sanur - Felicia Made Sabina Maya Mahadewi; Putu Diah Sastri Pitanatri; Ida Ayu Kalpikawati (Riviera Publishing, 2026)
This study aims to analyze the influence of green hotel implementation on environmental conservation in The Meru Sanur through waste reduction and employee participation. The study uses an explanatory quantitative approach with a survey method of operational employees in the housekeeping, food & beverage, front office, and engineering departments. The data were analyzed using multiple linear regression. The results of the study show that the implementation of green hotels has a positive but not significant influence on environmental conservation. The waste reduction variable also showed a positive but not significant influence. Meanwhile, employee participation had the strongest relationship with environmental conservation, with a correlation value of 0.410 and a significance of 0.025 (<0.05). These findings show that the success of green hotel programs is more influenced by active employee involvement than by technical and environmental policy aspects alone. Therefore, increased awareness, training, and employee engagement are important factors in supporting environmental sustainability in the hospitality industry.